Elevated CO(2) enhances aerobic scope of a coral reef fish - Rummer, Jodie L. (Conserv Physiol, 2013)
The uptake of anthropogenic CO(2) by the ocean has been suggested to impact marine ecosystems by decreasing the respiratory capacity of fish and other water breathers. We investigated the aerobic metabolic scope of the spiny damselfish, Acanthochromis polyacanthus, from the Great Barrier Reef, Australia when exposed for 17 days to CO(2) conditions predicted for the end of the century (946 μatm CO(2)). Surprisingly, resting O(2) consumption rates were significantly lower and maximal O(2) consumption rates significantly higher in high-CO(2)-exposed fish compared with control fish (451 μatm CO(2)). Consequently, high-CO(2)-exposed fish exhibited an unexpected increase in absolute (38%) and factorial aerobic scopes (47%). Haematological and muscle water changes associated with exercise were not affected by CO(2) treatment. Thus, contrary to predictions, our results suggest that elevated CO(2) may enhance aerobic scope of some fish species. Long-term experiments are now required to assess the response to elevated CO(2) further, because developmental and transgenerational effects can be dramatic in fish. Ultimately, understanding the variability among species regarding the effects of CO(2) on aerobic scope will be critical in predicting the impacts of ocean acidification on marine communities and ecosystems.